2020
DOI: 10.4103/ijoem.ijoem_259_19
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between noise annoyance and high blood pressure in workers exposed to chronic noise among the workers of an automotive industry

Abstract: Background: Chronic exposure to noise in workplaces is one of the most important physical agents that affects workers’ health and causes social and individual problems. The aim of this study was to investigate the relationship between noise annoyance and blood pressure (BP) of workers of an automotive industry. Methods: In this cross-sectional study, 250 workers were randomly selected. The subjects were classified in two groups based on the exposure to sound pressure le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…A recent study concluded that the level of sound pressure that is over 85 dB had mainly acute effects and psychological and physical damage. Only this sound level can lead to an increased risk of hypertension as well as otherwise cardiovascular diseases (Alimohammadi et al 2020 ). HO-1 protects against inflammatory and oxidative insults in case of hypertension in order to reduce blood pressure and end-organ damage through its expression at the vascular level and to shift macrophages toward anti-inflammatory phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study concluded that the level of sound pressure that is over 85 dB had mainly acute effects and psychological and physical damage. Only this sound level can lead to an increased risk of hypertension as well as otherwise cardiovascular diseases (Alimohammadi et al 2020 ). HO-1 protects against inflammatory and oxidative insults in case of hypertension in order to reduce blood pressure and end-organ damage through its expression at the vascular level and to shift macrophages toward anti-inflammatory phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…For staff, excessive noise stress is associated with suboptimal performance and burnout. [5][6][7][8][9][10][11][12] For infants, stress from noise increases the consumption of calories and disrupts normal growth and development. 6 These can contribute to increased length of NICU stay, need for rehabilitative care, and increased health care costs.…”
mentioning
confidence: 99%
“…Noise exerts stress on both staff and infants in the NICU. For staff, excessive noise stress is associated with suboptimal performance and burnout 5-12. For infants, stress from noise increases the consumption of calories and disrupts normal growth and development 6.…”
mentioning
confidence: 99%